Industrial leadership: Leading within the field of construction and design - Kasapoğlu, Esin (My University, 2017)
The structure of the design and construction organizations is different from that of the service or manufacturing industry. Although design and construction organizsations are parts of the construction industry, they are different from each other, also. This chapter is based on the researches investigating the leadership behaviours of construction professionals and consists basically of two main sections. In the first section, the concept of leadership and importance of leadership in design and construction processes will beis discussed. In this first section, firstlyinitially, as the leaders of the design teams, the importance of leadership skills of architects in both architectural design teams and other design teams, and, secondly, the importance of leadership skills of construction professionals will beis evaluated. In the second section, the focus of the study will befocuses on the evaluation of leadership behaviours of construction professionals with a literature review of previous researches. In this second section, initially, the leadership stiles in design teams, and secondly leadership stiles of construction teams will beis evaluated.
Keywords: Design; Construction; Design Team; Construction Team; Construction Project Management; Dizayn; İnşaat; Dizayn Takımı; İnşaat Proje Yönetimi